Comparison of Bacteriuria, Hematuria, and Pain Complications after Transrectal and Transperineal Prostate Biopsy in Patients with Suspected Prostate Cancer - Kurnia Penta Seputra; Harry Achsan Chaerul; Besut Daryanto; Dewi Santosaningsih; Khairul Asri Mohd Ghani (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Prostate cancer is the most common cancer in men with the second-highest mortality rate in the United States. In Indonesia, 1,102 patients with an average age of 67.18 years have been diagnosed with prostate cancer in the last 8 years. The primary diagnostic approach for prostate cancer involves two biopsy methods: transrectal prostate biopsy (TRPB) and transperineal prostate biopsy (TPPB). This study aims to evaluate the complications of bacteriuria, hematuria, and pain levels after the procedures between TRPB and TPPB. Methods. This study is an analytical observational study with a cohort design. The sample consists of 34 patients suspected of prostate cancer, undergoing prostate biopsy with a 1:1 technique comparison between TPPB (17) and TRPB (17). Data were analyzed using SPSS software version 28. Result. The Friedman test and paired T-test results show a significant difference in urine culture and urinalysis before and after transrectal biopsy, but no significant difference in pain assessment. For transperineal biopsy, a significant difference was only found in pain assessment before and after the biopsy. The Mann-Whitney test results show a significant difference in the incidence of bacteriuria and hematuria, with TPPB showing lower rates and higher VAS in the TPPB group. Conclusion. TPPB tends to be better at avoiding the risk of bleeding and infection complications, while TRPB is better at avoiding pain. Therefore, TPPB is more beneficial for patients.